The Fulfilment of Legal Identity: A Case Study of Residents Without Population Identification Numbers - Jati, Fardi Prabowo (Universitas Brawijaya, 2024)
Legal identity is crucial for individuals as it establishes their rights and obligations as legal subjects. Despite its importance, many residents in Yogyakarta lack a legal identity. This research aims to analyse the regulations governing the provision of legal identity for residents without a population identification number (NIK) and to identify the causes behind this issue in Yogyakarta. This study employs non-doctrinal legal research, combining normative and empirical methods. The findings reveal that obtaining a NIK is essential for fulfilling human rights and constitutional rights. This process involves population registration, which begins with recording the individual’s biodata. Changes in the population administration information system have led to the exclusion of residents who have not completed biometric recording from the population database, resulting in a lack of legal identity. In Yogyakarta, two main factors contribute to the absence of NIKs: First, impoverished individuals with domicile issues caused by the costs and time required for domicile relocation, potential trafficking, homelessness, and loss of family card data. Second, individuals with disabilities who are unable to complete the registration process.